Celiac Disease in Patients with Type 1 Diabetes Mellitus: Genetics, Biochemical Features, and Serological Markers - Ban Waheed Hussein Bdair; Sarmad Jaafar Mohammed Alrubaye; Satar Jabbar Rahi Algraittee (American Journal of Biodiversity, 2025)
The prevalence of celiac disease (CD) is significantly higher in patients with Type 1 diabetes mellitus (T1DM) compared to the general population and as a result, the interrelationship of these two autoimmune disorders has attracted the interest of many researchers over the years. The most pressing questions have been whether the concomitant existence of CD pose challenges to the management of T1DM. Therefore, this study evaluated the diagnostic parameters for T1DM in patients with T1DM and CD. Forty-five patients with T1DM only, 45 with T1DM + CD were recruited for this study and their demographical, anthropometric, biochemical features, and expression of HLA-DQ2 and DQ8 genes were measured. Serum levels of anti-glutamic acid decarboxylase (GAD) autoantibody and c-peptide were also evaluated. The results obtained showed significant differences in ferritin (6.31±0.83 μg/L T1DM vs. 5.43±0.31 μg/L T1DM + CD), vitamin D3 (7.15±0.99 ng/mL T1DM vs. 11.04±2.82 ng/dL T1DM + CD), urea (35.23±4.36 mg/dL T1DM vs. 23.24±4.75 mg/dL T1DM + CD) and creatinine (1.06±0.06 mg/dL T1DM vs. 0.61±0.01 mg/dL T1DM + CD). Homozygosity to HLA-DQ2 was 11% in T1DM against 31.1% in the T1DM + CD group, 80 % of T1DM + CD patients were HLA-DQ2/DQ8 heterozygotes, while 20 % had HLA-DQ2 gene only with none having the HLA-DQ8 haplotype. Homozygosity to HLA-DQ8 was 57.8 % in the T1DM patients. Seropositivity to anti-GAD was 26.6 % in T1DM patients compared to 31.1% in T1DM + CD group. while the proportion of patients with below normal C-peptide levels in the T1DM + CD group was 66.6 % which is lower than 77.7% recorded for the T1DM group. Anti-GAD levels were significantly higher in patients with T1DM only compared with those with CD+T1DM (p < 0.05). From the findings, it was inferred that the concomitant existence of T1DM and CD may result to difficulty in glycemic control and the pre-existence of CD may trigger the pathogenesis/ initiation of T1DM. Therefore, this study recommends that the early diagnosis of T1DM should be sufficient to warrant suspicion of subclinical CD.